Biomass consumption and CO2, CO and main hydrocarbon gas emissions in an Amazonian forest clearing fire - Soares Neto, T. G.; Carvalho, J. A. [UNESP]; Veras, C. A. G.; Alvarado, E. C.; Gielow, R.; Lincoln, E. N.; Christian, T. J.; Yokelson, R. J.; Santos, J. C. (Pergamon-Elsevier B.V. Ltd, 2009)
Biomass consumption and CO2, CO and hydrocarbon gas emissions in an Amazonian forest clearing fire are presented and discussed. The experiment was conducted in the arc of deforestation, near the city of Alta Floresta, state of Mato Grosso, Brazil. The average carbon content of dry biomass was 48% and the estimated average moisture content of fresh biomass was 42% on wet weight basis. The fresh biomass and the amount of carbon on the ground before burning were estimated as 528 t ha(-1) and 147 t ha(-1), respectively. The overall biomass consumption for the experiment was estimated as 23.9%. A series of experiment in the same region resulted in average efficiency of 40% for areas of same size and 50% for larger areas. The lower efficiency obtained in the burn reported here occurred possibly due to rain before the experiment. Excess mixing ratios were measured for CO2, CO, CH4, C-2-C-3 aliphatic hydrocarbons, and PM2.5. Excess mixing ratios of CH4 and C-2-C-3 hydrocarbons were linearly correlated with those of CO. The average emission factors of CO2, CO, CH4, NMHC, and PM2.5 were 1,599, 111.3, 9.2, 5.6, and 4.8 g kg(-1) of burned dry biomass, respectively. One hectare of burned forest released about 117,000 kg of CO2, 8100 kg of CO, 675 kg of CH4, 407 kg of NMHC and 354 kg of PM2.5. (C) 2008 Published by Elsevier Ltd.
Keywords: Biomass consumption; Gas emission; Amazonian forest fires